STUDI TENTANG SANITASI LINGKUNGAN SEKOLAH DASAR NEGERI DI KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Andriani, Dina; Rianto, Slamet; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
This study aimed to obtain information, analyze and discuss data on Environmental Sanitation Public Elementary School in Sungai Beremas District. Pasaman Barat. This type of research is descriptive. The study population was all Heads of State Elementary School in Sungai Beremas District a total of 11 people. The study sample in this study were taken with a total sampling techniques so that a total of 11 samples. Based on the analysis of the data it can be concluded as follows: (1) The condition of water supply facilities in the environment Elementary School Sungai Beremas District of poor condition of water supply facilities by including the percentage 31,82%, (2) condition of garbage disposal facilities in the environment Elementary School at Sungai Beremas District include either the percentage of waste disposal facilities condition of 68,18%, (3) condition of human waste disposal facilities or toilets in the environment Elementary School Sungai Beremas District including both the percentage of the condition of human waste disposal facilities by 65,91%, and (4) the sanitary conditions of food and drinks public elementary school in Sungai Beremas district include well with the percentage of sanitary conditions of food and drinks at 76.14%